Mayhem on the Marzipan Express - Connolly, Rebecca (Connolly, Rebecca. Claire Walker mystery., 2026)
"A romantic getaway through the Scottish Highlands turns deadly when a passenger on the train is murdered--and a famous chef is the prime suspect. Amateur baker and part-time sleuth Claire Walker may not have won Britian's Battle of the Bakers cooking competition, but she still went home with a grand prize: Jonathan Ainsley's heart. The happy couple boards the famed Scottish train, the Mallaig Steam Express-temporarily renamed "The Marzipan Express" in honor of famed chef Alan Gables, who is hosting an exclusive culinary experience for his most devoted fans. Claire is delighted to serve as Alan's sous-chef for the trip, hoping to learn some baking tips from the master. The trip has barely begun when the train screeches to a halt. The engine has malfunctioned and must be repaired. While Claire and Jonny explore the train, they discover a dead body in one of the dining cars. It appears to be an accident, but Claire can sense something is wrong as easily as she can sense an overbaked soufflé. When the clues all point to Alan as the culprit, Claire and Jonny decide to investigate on their own. Unfortunately, Alan doesn't have an alibi, his assistant is oddly nervous around him, and a shadowy figure keeps appearing at all the wrong times. Could it be someone from Alan's past trying to frame him? Or could Alan be trying to cover his tracks? Claire had hoped for a delicious, romantic getaway, not investigating a mysterious death while stress-eating trifle in the kitchen car and trying to not be jealous of a magazine reporter who is flirting with Jonny. It's mayhem in more ways than one. "--